The current state of road traffic in the city of osh and ways to improve it (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article analyzes the current state of road traffic and transportation problems in the city of Osh. The main objective of the study was to identify the causes of traffic congestion resulting from the increasing number of motor vehicles in the city and to propose scientifically based solutions. The conducted research revealed that in recent years, Osh has experienced a significant growth in traffic flow. This situation has created serious difficulties for both drivers and pedestrians. The most pressing issues include traffic congestion, insufficient public transport, and a decline in road safety. The authors analyzed these problems and, as a result, proposed possible solutions.
Keywords: Osh city, traffic, transportation problems, road safety, digital technologies, traffic congestion.